Biosafety Test for Plant Growth-Promoting Bacteria: Proposed Environmental and Human Safety Index (EHSI) Protocol - Vílchez, Juan I.; Navas, Alfonso; González-López, Jesús; Arcos, Susana C.; Manzanera, Maximino (Frontiers in Microbiology, 2016)
Plant growth-promoting bacteria (PGPB) colonize plants and enhance their growth by different mechanisms. Some of these microorganisms may represent a potential threat to human, animal or plant health; however, their use might be approved in parts of Europe if they have been recommended as plant growth enhancers. The current regulatory framework has resulted in a fragmented, contradictory system, and there is an urgent need to establish harmonized protocols for the predictability, efficiency, consistency and especially the safety of PGPB for human and animal health and for the environment. In response to current efforts to update biosafety policies and provide alternative methods to replace the use of vertebrate animals, we propose a panel of tests and an evaluation system to reliably determine the biosafety of bacterial strains used as PGPB. Based on the results of different tests, we propose a scoring system to evaluate the safety of candidates for PGPB within the limitations of the assays used.